2022
DOI: 10.1155/2022/8735099
|View full text |Cite|
|
Sign up to set email alerts
|

A Retrospective Analysis of Internet-Based Sharing Nursing Service Appointment Data

Abstract: Aims. To investigate the historical data of the “Internet+ Nursing” service platform and provide a theoretical basis to optimize the “Internet+ Nursing” service model by analyzing a population in need of nursing care services, service prices, services in demand, willingness to place orders, and feedback on use. Methods. A retrospective analysis of data related to home care services on the “Jiuzhou Nursing Care” platform from April 2020 to August 2021, a total of 279 person-times, relevant information about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This may be related to the aging population and more comorbidities in the elderly: According to the National Bureau of Statistics, by the end of 2022, the elderly population aged 60 or above in China numbered 280.04 million, accounting for 19.8% of the total population. In addition, 150 million elderly people suffer from chronic diseases, accounting for 65% of the total elderly population, and about 40 million elderly people are disabled or semi-disabled, resulting in a rapidly growing demand for home care [ 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be related to the aging population and more comorbidities in the elderly: According to the National Bureau of Statistics, by the end of 2022, the elderly population aged 60 or above in China numbered 280.04 million, accounting for 19.8% of the total population. In addition, 150 million elderly people suffer from chronic diseases, accounting for 65% of the total elderly population, and about 40 million elderly people are disabled or semi-disabled, resulting in a rapidly growing demand for home care [ 17 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%